Detection of Plasmodium in small ruminants in Yogyakarta, Indonesia, using a nested PCR assay - DWI PRIYOWIDODO; APRIL HARI WARDHANA; DYAH HARYUNINGTYAS SAWITRI; JOKO PRASTOWO; WISNU NURCAHYO; AAN AWALUDIN; YUDHI RATNA NUGRAHENI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Priyowidodo D, Wardhana AH, Sawitri DH, Prastowo J, Nurcahyo W, Awaludin A, Nugraheni YR. 2023. Detection of Plasmodium in small ruminants in Yogyakarta, Indonesia, using a nested PCR assay. Biodiversitas 24: 6722-6726. Limited investigation of natural malaria infection in small ruminants in Yogyakarta needs to be explored. Plasmodium sp., as the causative agent of malaria, has been proven to infect ungulates, including small ruminants. This study aimed to investigate the presence of natural malaria infection in goats and sheep in Yogyakarta. A total of 303 blood samples were collected from goats and sheep in this study from four selected areas by a cross-sectional study. A microscopic examination detected the Plasmodium stage in a thin blood smear. Nested Polymerase Chain Reaction (PCR) performed molecular detection, targeting cytochrome b (cytb) as a gene target. It was found that no Plasmodium stage was detected in thin blood smears. However, three out of 70 blood samples from Girimulyo were Plasmodium-positive based on nested PCR assay. The results highlight that molecular assay by nested PCR is more sensitive than microscopic examination. Molecular analysis revealed natural Plasmodium infections in Ettawa cross-bread goats, with a proportion of 0.0429 (95% CI: 0.0089-0.1202). There was no statistical difference between sex and natural malaria infection in goats. This finding suggests that molecular analysis is necessary to detect natural malaria infection with extremely low parasitemia levels. Therefore, further study with larger sample sizes and broader geographical representation is needed to fully understand these malaria infections in goats and sheep.